Carta abierta a Hans Christian Andersen en el bicentenario de su nacimiento - Rubio Torres, Carlos (2005)
April 2nd, 2005 was a day for a double celebration: the bicentennial of the birth of Danish writer Hans Christian Andersen and the International Children’s Book Day. Andersen is known as the creator of contemporary children literature, for his fairy tales introduce language that at that time was used by adults only. Students from Central American University (UCA) in Managua, Nicaragua, read an “Open Letter” during a Festival that the Books for Children Foundation organized in honor of the author along with the Norwegian and Danish embassies. The letter presents Andersen’s biography and explores alternative readings of his fairy tales from educational, psychological and psychoanalytical perspectives. The letter concludes with an interpretation of Andersen as a metaphor for the understanding and dialogue between Costa Rica and Nicaragua.